Pengaruh Komitmen dan Peran Pengelola Keuangan Terhadap Kinerja (Studi pada Pengelola Keuangan SKPK di Pemerintahan Kabupaten Aceh Timur) - Muhammad Jamil; Teuku Muana Refi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2021)
This study aims to determine the impact of responsibilities and roles on implementation. This examination was led by the SKPK within the East Aceh Regional Government. The sample of this audit data is 49 echelon IV financial administration officials who were taken for strategic audit purposes. Information is collected using surveys and then the information is checked using various direct relapse techniques. This investigation traces that the responsibilities of the chief financial officer and the department together affect the performance of the financial supervisor. The responsibilities of the financial supervisor positively affect the finance director. Part of the financial supervisor does not affect the finance director.